Efficiently photocatalytic conversion of CO2 on ultrathin metal phthalocyanine/g-C3N4 heterojunctions by promoting charge transfer and CO2 activation - Sun, Jiawen; Bian, Ji; Li, Jiadong; Zhang, Ziqing; Li, Zhijun; Qu, Yang; Bai, Linlu; Yang, Zhao-Di; Jing, Liqiang (Applied catalysis. B, Environmental, 2020)
[Display omitted] •Ultrathin dimension-matched MPc/T-CN heterojunctions are controllably synthesized.•CuPc is highly dispersed on T-CN via formed H-bonding by surface hydroxyl-induced assembly.•The optimized heterojunction exhibits about 10-fold improved photoactivity for CO2 reduction.•The exceptional photoactivity is attributed to the promotion of charge transfer and CO2 activation.•An unexpected HLEE transfer mechanism with catalytic function of M2+ in MPc/CN system is proposed. Herein, ultrathin dimension-matched metal phthalocyanine/treated g-C3N4 (MPc/T-CN) heterojunctions with exceptional photocatalytic activities for converting CO2 to CO and CH4 have been controllably constructed through a facile surface hydroxyl group-induced assembly process, in which the increased amount of hydroxyl group by treating g-C3N4 nanosheets with HNO3 solution is much crucial for this successful assembly to improve the interfacial connection via the formed hydrogen bonding. Among the used MPc, CuPc is the best modifier for T-CN comprehensively dependent on the promotion for charge transfer and CO2 activation based on the theoretical and experimental results. The photocatalytic activity of optimized CuPc/T-CN heterojunction is about 10-fold improvement under UV–vis light irradiation compared with that of pristine CN, mainly attributed to the unexpected transfer of excited high- level-energy electrons (HLEEs) from T-CN to the ligand of CuPc and then to the central metal ions (Cu2+) with potential catalytic function for CO2 reduction reactions.